2019
DOI: 10.3390/su11133685
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Effects of Vegetation on the Characteristics of Runoff and Sediment Yield on Riparian Slope along the Lower Yellow River

Abstract: Riparian vegetation plays a vital role in soil and water conservation and river health maintenance. However, its inhibiting effects on water and soil loss are limited by different factors, such as slope gradient, vegetation coverage and their interaction. Therefore, this study quantified the inhibiting effect of riparian vegetation on the runoff, sediment and hydraulic characteristics of overland flow, and assessed its relative contribution to slope gradient. Specifically, we selected a riparian slope along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
2
4
0
Order By: Relevance
“…Additionally, it is a rainwater-absorbing reservoir. This assertion is consistent with that of [38][39][40], who identified tree size, vegetation cover and tree density as the essential plant component influencing water-holding capacity for minimizing soil nutrient leaching. The positive link between girth and sediment loss on the 5-year-old fallow is not unexpected since the bushes' girth was not sufficiently established to function as a physical barrier against precipitation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, it is a rainwater-absorbing reservoir. This assertion is consistent with that of [38][39][40], who identified tree size, vegetation cover and tree density as the essential plant component influencing water-holding capacity for minimizing soil nutrient leaching. The positive link between girth and sediment loss on the 5-year-old fallow is not unexpected since the bushes' girth was not sufficiently established to function as a physical barrier against precipitation.…”
Section: Discussionsupporting
confidence: 90%
“…This agrees with the findings of [37] that vegetation regulates hydrological processes significantly. Moreover, Wu et al [11,38] noted that the presence and growth of vegetation attributes decreases runoff and sediment loss. Similarly, Wu et al [11] and Iwara [4] stated that crown cover lessens the negative influence of rainfall on the land and soil by intercepting and holding a significant amount of their energy.…”
Section: Discussionmentioning
confidence: 99%
“…There were two primary causes for this variation: the reduction in raindrop kinetic energy associated with the increase in coverage density and the increase in runoff resistance due to the higher coverage density of vegetation. Zhang et al (2019) also reported similar results. Nevertheless, Zhu et al (2010) found that the runoff and erosion rates decreased with increasing coverage density when the coverage density was lower than 60%; conversely, the runoff and erosion rates exhibited increasing trends.…”
Section: Effects Of the Grass Canopy And Root On The Runoff Rate And Erosion Ratesupporting
confidence: 64%
“…High vegetation connectivity helped maintain river water quality. Vegetation around riverbanks helped remediate pollutants carried by water runoff, and other water flows entering the river [15,16]. If there was little vegetation, the pollutant residue could not be remedied, resulting in water and soil pollution.…”
Section: Resultsmentioning
confidence: 99%